Death Penalty as State Crime: Examining the Physical and Mental Health Concerns with Capital Punishment in the U.S. - Finley, Laura (In Factis Pax: Journal of Peace Education and Social Justice, 2022)
This paper begins with a review of the relevant literature on state crime. It then focuses on the physical health concerns related to the methods used to execute individuals in the U.S. Lethal injection is the primary method used today, yet there are a host of issues related to the chemicals used in lethal injections, how states are obtaining them illegally, and the protocol for lethal injections. In addition, while there has been some case law on executing those with intellectual disabilities or those who struggle with mental health, there is no categorical prohibition on executing people who suffer from severe mental illness. This not only violates international human rights laws but because these mental health issues are well-known to those who oversee executions and the legislative and judicial bodies that authorize them, they can also be seen as crimes of the state. The paper concludes with a review of how abolitionist groups should proceed.